2021
DOI: 10.7717/peerj.11726
|View full text |Cite
|
Sign up to set email alerts
|

Enteroaggregative Escherichia coli is associated with antibiotic resistance and urinary tract infection symptomatology

Abstract: Background Uropathogenic Escherichia coli (UPEC) is the causative agent of uncomplicated urinary tract infections (UTIs) in ambulatory patients. However, enteroaggregative E. coli (EAEC), an emergent bacterial pathogen that causes persistent diarrhoea, has recently been associated with UTIs. The aim of this study was to determine the frequency of EAEC virulence genes, antibiotic resistance, as well as biofilm production of UPEC isolates obtained from ambulatory patients with non-complicated UTIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…We found that the genes were present not only in isolates from symptomatic but also from asymptomatic patients. We also found that these genes are more frequent in phylogroups B2, D, and F. The difference between our results and those reported by Nielsen et al may be explained because we included patients with AB, as well as patients with ailments (type 2 diabetes mellitus, pregnancy, catheter, and chronic renal illness) ( Martinez-Santos et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…We found that the genes were present not only in isolates from symptomatic but also from asymptomatic patients. We also found that these genes are more frequent in phylogroups B2, D, and F. The difference between our results and those reported by Nielsen et al may be explained because we included patients with AB, as well as patients with ailments (type 2 diabetes mellitus, pregnancy, catheter, and chronic renal illness) ( Martinez-Santos et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 91%
“…Some UPEC virulence factors, such as Cnf1 and HlyA, have been associated with UTI symptoms ( Martinez-Santos et al, 2021 ); therefore, we analyzed whether there was any relationship between the expression of the ECUMN genes and disease symptoms. Interestingly, we found no relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the resistance profile of hybrid UPEC/EAEC and UPEC/aEPEC isolates are scarce in the literature. However, a very recently published article characterizing UPEC isolates obtained from 100 ambulatory patients with community-acquired UTIs in the city of Chilpancingo, Mexico, reported that 77.27% (17/22) of the UPEC/EAEC hybrid isolates studied were classified as ESBL producers, besides the high resistance rates observed for β-lactams, aminoglycosides, quinolones/fluoroquinolones, and folic acid metabolism inhibitors [ 73 ]. Moreover, a hybrid UPEC/aEPEC identified as an ESBL-producer, and harboring the bla CTX-M-15 gene, was reported as a causative agent of UTI in Brazil [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the World Health Organization (WHO) published the first estimates of FBD worldwide reporting that E. coli caused over 110 million cases of FBD resulting in over 63,000 deaths (WHO, 2015). Diarrhoeagenic E. coli (DEC) pathotypes including enteropathogenic (EPEC) and atypical EPEC (lacking the bundle-forming pilus), enterotoxigenic (ETEC), enteroaggregative (EAEC), diffusely adherent (DAEC) entero-invasive (EIEC), and Shiga toxin-producing E. coli (STEC), are important causes of diarrhoea in children, of travellers’ diarrhoea (TD), and diarrhoea in immunocompromised patients (Martínez-Santos et al, 2021). STEC can be specifically associated with haemolytic uremic syndrome, while ETEC and EAEC with TD (Cabrera-Sosa & Ochoa, 2020; Jiang & DuPont, 2017).…”
Section: Overview Of Intestinal Foodborne Diseasesmentioning
confidence: 99%